2018
DOI: 10.1007/s00066-018-1338-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of accelerated Linac-based SBRT in five consecutive fractions for localized prostate cancer

Abstract: Accelerated SBRT for low-intermediate PC is feasible and well tolerated with comparable oncological outcome as described for other series with the same RT technique but treatment delivery on every other day. Longer follow-up is needed to the assess late toxicity profile and long-term clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…Of note, a clear relationship between the delivered dose and the occurrence of late grade ≥ 3 GU toxicity has been demonstrated in a meta‐regression analysis of 5127 patients treated with prostate SBRT . This was confirmed by the low GU toxicity rates, comparable to our study, observed in 18 patients treated in a phase II SBRT trial delivering 37.5 Gy in 5 consecutive fractions to the prostate and between 33.2 and 35 Gy to the urethra …”
Section: Discussionsupporting
confidence: 87%
“…Of note, a clear relationship between the delivered dose and the occurrence of late grade ≥ 3 GU toxicity has been demonstrated in a meta‐regression analysis of 5127 patients treated with prostate SBRT . This was confirmed by the low GU toxicity rates, comparable to our study, observed in 18 patients treated in a phase II SBRT trial delivering 37.5 Gy in 5 consecutive fractions to the prostate and between 33.2 and 35 Gy to the urethra …”
Section: Discussionsupporting
confidence: 87%
“…In the case of low-risk PC, the clinical target volume (CTV) was the prostate gland only, whereas in the case of intermediate-risk PC, the entirety of the seminal vesicles (SV) was included. The planning target volume (PTV) consisted of CTV + 5 mm margins in each direction, except 3 mm posteriorly, according to previously published experiences [12]. As organs at risk, the rectum, bladder, penile bulb, urethra, and femoral heads were delineated.…”
Section: T Mr-guided Radiotherapymentioning
confidence: 99%
“…Moreover, since 2014, the National Comprehensive Cancer Network (NCCN) Guidelines [9] have stated that, in centers with appropriate technology and expertise, extreme hypofractionated treatment could be considered as a potential option to offer for selected localized PC. Since then, more robust evidence and new technological platforms are consolidating the role of extreme hypofractionation (also known as stereotactic body radiotherapy -SBRT) for localized PC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of low-risk PC, the clinical target volume (CTV) was the prostate gland only, whereas in the case of intermediaterisk PC, the entirety of the seminal vesicles (SV) was included. The planning target volume (PTV) consisted of CTV +5mm margins in each direction, except 3mm posteriorly, according to previously published experiences [12]. As organs at risk, the rectum, bladder, penile bulb, urethra, and femoral heads were delineated.…”
Section: 5t Mr-guided Radiotherapymentioning
confidence: 99%
“…Guidelines [9] have stated that, in centers with appropriate technology and expertise, extreme hypofractionated treatment could be considered as a potential option to offer for selected localized PC. Since then, more robust evidence and new technological platforms are consolidating the role of extreme hypofractionation (also known as stereotactic body radiotherapy -SBRT) for localized PC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%